Poética del cuento moderno de Flores nocturnas de Miguel Bances - Bances Gandarillas, Miguel Luis (2019)
This article tries to establish the poetics of the story book Flores nocturnas by Miguel Bances. It is based on the idea that the intellectual exercise, which supposes the reflection of the work by the author, should separate from the general ideas and that the story, character and language notions should be considered in a greater depth. Firstly, the reflection on two paradigms of the modern story (Poe and Chéjov) is proposed in order to establish links with the genre of the story. Secondly, the ascription of the stories of Flores Nocturnas with the epiphanic story is sought. Thirdly, it is suggested that the character should be studied from a critical perspective which proposes the subject-modernity relationship. Finally, the view of reality is discussed based on the language notion used in Flores Nocturnas.